2012
DOI: 10.1016/j.bpj.2012.06.038
|View full text |Cite
|
Sign up to set email alerts
|

Measuring Molecular Motor Forces In Vivo: Implications for Tug-of-War Models of Bidirectional Transport

Abstract: Molecular motor proteins use the energy released from ATP hydrolysis to generate force and haul cargoes along cytoskeletal filaments. Thus, measuring the force motors generate amounts to directly probing their function. We report on optical trapping methodology capable of making precise in vivo stall-force measurements of individual cargoes hauled by molecular motors in their native environment. Despite routine measurement of motor forces in vitro, performing and calibrating such measurements in vivo has been … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

11
177
6
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 130 publications
(209 citation statements)
references
References 54 publications
11
177
6
1
Order By: Relevance
“…Similar "memory" has recently also been shown for lipid droplets in optical manipulation experiments (24). These studies showed that after pulling the lipid droplet off the microtubule by optical tweezers and allowing it to reattach, the majority of lipid droplets continued to move in the same direction.…”
Section: Conclusion and Discussionsupporting
confidence: 69%
“…Similar "memory" has recently also been shown for lipid droplets in optical manipulation experiments (24). These studies showed that after pulling the lipid droplet off the microtubule by optical tweezers and allowing it to reattach, the majority of lipid droplets continued to move in the same direction.…”
Section: Conclusion and Discussionsupporting
confidence: 69%
“…Thus, our current result provides a strong support for the idea that besides its binding to other subunits, the tail is important for regulating dynein motor function in vivo. It is worth pointing out that in vivo, the dynein motor carrying a cargo not only needs to move in a cytoplasm with considerable viscosity (63,64) but also needs to compete with plus-end-directed motors bound to the same cargo (65)(66)(67). In filamentous fungi, kinesin-3 is able to bind to the dynein-bound early endosome and be carried to the minus end as a cargo of dynein (40,53,68).…”
Section: Discussionmentioning
confidence: 99%
“…Some authors [215] report for example that stall forces are completely different in vivo, and in particular that they become similar for dyneins and kinesins [223] (which have quite different stall forces in vitro). The origin of these differences are so far not understood.…”
Section: In Vitro Versus In Vivomentioning
confidence: 99%
“…Experimental evidence for the attachment of many motors is based on a number of observations, in particular based on force measurements [345,351,215,223]. Another argument is that, for several motor-cargo systems, there is evidence for bidirectional non diffusive motion [388].…”
Section: Motor-cargo Complexesmentioning
confidence: 99%